Design of Test Signals for Identification of Neuromuscular Admittance. Issue 19 (2016) - Bhoelai, Anand K.; van Paassen, M.M. (René); Abbink, David A.; Mulder, Max
Abstract: The human neuromuscular system can be seen as a versatile and extremely adaptive actuator. Through co-contraction and reex modulation, the properties of the neuromuscular system can be modified, leading to a change in movement response to externally applied forces. These properties are normally expressed in the form of the neuromuscular admittance. In a series of standard tasks, the force-, relax-, and position-task admittance of the neuromuscular system can be identified. However, the test signals used in these tasks can also limit the range of reex adaptation possible and wrong choice can create a phenomenon analogous to cross-over regression in manual control tasks, and force the human to use only a limited range of the possible reex adaptation. This paper presents a systematic investigation, through a model study, of the inuence of test signals on the range of reex adaptation. For this, criteria for test signal acceptability have been developed. The method is applied to the currently used test signals consisting of a high and a low shelf, and enables the selection of the high shelf bandwidth.